POTENSI EKSTRAK TUMBUHAN ANDALIMAN (Zanthoxylum acanthopodium DC.) SEBAGAI ANTIBAKTERI Staphylococcus aureus - Oma Sepriani; Nurhamidah Nirhamidah; Dewi Handayani (ALOTROP, 2020)
The aims of this study is to determine the secondary metabolite compounds in Roots, stem bark, leaves and fruit of Andaliman (Zanthoxylum acanthopodium DC), and determine the most potent part of Andaliman plant extract in inhibiting the growth of Staphylococcus aureus bacteria. Andaliman plant taken in Simarpingan, Sipaholon village sub district of North Sumatra. Part of the Andaliman plantar are cleaned, cut into small pieces and then dried and mashed, samples that have been finely phytochemically tested and extracted. Testing of secondary metabolite compound by doing phytochemical screening of roots, stem bark, leaves and fruit of Andaliman, alkaloid test using meyers reagent, terpenoid test and steroid using TLC plate with eluent n-hexana : ethyl acetate with ratio 6:4, flavonoid test using soluton HCl and Mg band, saponin test using soap test, tannin test using ferro (III) chloride solution. Test of antibacterial activity using disc diffusion method. Phytochemical results showed that all parts of the plant andaliman contain secondary metabolite compounds namely alkaloids, flavonoids, terpenoids, tannins and also saponins. The result of antibacterial activity test of leaf extract of leaf and leaf which has the most potential as antibacterial of S.aureus is bark. Because it able to inhibit S.aureus growth with 11 mm inhibition zone at concentration 5x104 ppm, which is included in the strong category. In addition to skin of andaliman leaf stem is also potential as an antibacterial with a 10 mm inhibition zone at concentration 5x104 ppm, which is included in the medium category.